2018
DOI: 10.1108/jmd-09-2017-0294
|View full text |Cite
|
Sign up to set email alerts
|

Explicit preferred leader behaviours across cultures

Abstract: Purpose The purpose of this paper is to develop a reliable and valid field survey research instrument to assess national cultural cognitive templates of preferred leader behaviour dimensions to facilitate education, development, and training of managerial leaders operating across diverse organisations. Design/methodology/approach The study consists of focus group evaluations of the validity and the translations to local languages of a survey instrument assessing leader behaviour preferences in business organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Dorfman et al (1997) propose that the phenomenon of leadership is universal across cultures, but that the way in which it is operationalized is culturally specific, supported by Hofstede (2001) and Littrell et al (2018). Project GLOBE (House et al , 2004) provides compelling evidence that business people within cultural groups agree in their beliefs about leadership such that there are statistically significant differences between preferred leader behavior templates in societal cultures.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Dorfman et al (1997) propose that the phenomenon of leadership is universal across cultures, but that the way in which it is operationalized is culturally specific, supported by Hofstede (2001) and Littrell et al (2018). Project GLOBE (House et al , 2004) provides compelling evidence that business people within cultural groups agree in their beliefs about leadership such that there are statistically significant differences between preferred leader behavior templates in societal cultures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An increasing body of evidence speaks of the importance of understanding culturally influenced leader behavior preferences (Littrell et al , 2018; Mustafa and Lines, 2016). Hofstede (2001), House et al (2004) and Littrell (2013) are among the seminal researchers who have found strong connections between leadership dimensions and cultural norms and values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards implications of this study for future researches in the domain of leadership, researchers might consider surveying multiple geographical areas in order to pull significant samples in different demographics. There are other instruments that could result in a broader variety of preferred leadership behaviors (for example, see Littrell, et al 2018).…”
Section: Implications Of the Studymentioning
confidence: 99%
“…Moreover, they suggested that the LBDQ-XII has "the highest validities averaged across the overarching dimensions of Consideration and Initiating Structure of their exhaustive array of studies reviewed" (Littrell, 2010, p. 169). Furthermore, there are extensive reliability studies (see Littrell, 2010Littrell, , 2013 of the LBDQ-XII which included Cronbach's α-based reliability analysis and item-to-scale correlational analyses, together with goodness-of-fit tests using structural equations modelling (SEM) (Littrell et al, 2018). 1, 11, 21, 31, 41 0.764 F2 51, 61, 71, 81, 91 0.697 F3 2, 12, 22, 32, 42, 52, 62*, 72, 82, 92 0.517 F4 3, 13, 23, 33, 43, 53, 63, 73, 83, 93 0.813 F5 4, 14, 24, 34, 44, 54, 64, 74, 84, 94 0.705 F6 5, 15, 25, 35, 45, 55, 65, 75, 85, 95 0.686 F7 6, 16, 26, 36, 46, 56, 66, 76, 86, 96 0.713 F8 7, 17, 27, 37, 47, 57, 67, 77, 87, 97 0.705 F9 8, 18, 28, 38, 48, 58, 68, 78, 88, 98 0.634 F10 9, 29, 49, 59, 89 0.717 F11 19, 39, 69, 79, 99 0.804 F12 10, 20, 30, 40, 50, 60, 70, 80, 90, 100 0.727 George and Mallery (2016, p. 231) provide the rule of thumb for Cronbach alphas, namely 0.9: Excellent, 0.8: Good, 0.7: Acceptable, 0.6: Questionable, 0.5: Poor, and <0.5: Unacceptable.…”
Section: Validity and Reliability Of The Surveymentioning
confidence: 99%